Working With a Student Model in a Creative Non-Fiction Workshop: Charging Joint Creativity (LEARNing Landscapes, 2012)
In this arts-based inquiry, I examine how a student model creative non-fiction essay develops students in a third-year creative writing workshop as critical readers, editors, and writers. Over the course of two semesters, student writers reciprocally acquire strategic knowledge and enhance their creativity. Plural voices emerge in the dialogue between the model student/writer, her peers, and my curriculum as evidenced in the narrative excerpts composed and revised by the student; in her peers’ critical feedback; and in students’ reflections. Exploring this collaboration, I envision affording more opportunity for student model writers to share their evolving knowledge in both traditional and online classrooms.
Keywords: arts-based; creative writing; student writer; creativity; narrative; student model